Brain atrophy in cerebral small vessel diseases: Extent, consequences, technical limitations and perspectives: The HARNESS initiative. Issue 2 (February 2020) - De Guio, François; Duering, Marco; Fazekas, Franz; De Leeuw, Frank-Erik; Greenberg, Steven M; Pantoni, Leonardo; Aghetti, Agnès; Smith, Eric E; Wardlaw, Joanna; Jouvent, Eric
Brain atrophy is increasingly evaluated in cerebral small vessel diseases. We aim at systematically reviewing the available data regarding its extent, correlates and cognitive consequences. Given that in this context, brain atrophy measures might be biased, the first part of the review focuses on technical aspects. Thereafter, data from the literature are analyzed in light of these potential limitations, to better understand the relationships between brain atrophy and other MRI markers of cerebral small vessel diseases. In the last part, we review the links between brain atrophy and cognitive alterations in patients with cerebral small vessel diseases.